The factors of risk of the development of endothelium dysfunction that people with hereditary atherosclerosis and coronary atherosclerosis have - I. A. Kovalev; G. I. Martsinkevich; T. E. Suslova; G. P. Philippov; V. N. Kim (Бюллетень сибирской медицины)
The research is devoted to the evaluation of the depressor and constrictive components of the vascular reactiveness in the people with burdened heredity on atherosclerosis and the factors of risk of this disease’s development. The connection of the vascular reactiveness of peripheral arteries with the factors of risk of atherosclerosis development is discovered. The results of researches allow to suppose that atherogenic factions of lipoproteins, inflammatory cytokines produced by mononuclear of nitric oxide participate in the formation of pathological vascular reactions in people with atherosclerosis and with burdened atherosclerosis heredity on preclinical disease level.